DAMPAK PENGGUNAAN TEKNOLOGI INFORMASI DALAM PELAKSANAAN LAYANAN BIMBINGAN DAN KONSELING OLEH GURU BK DI SMKN 1 SUMBAR - Diana Afifa; Mori Dianto; Yasrial Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is entitled "The Impact of Using Information Technology in the Implementation of Guidance and Counseling Services by Guidance and Counseling Teachers at SMKN 1 Sumbar". The background of this study is based on the increasingly rapid development of information technology and its influence on the world of education, including in the implementation of guidance and counseling (BK) services. The use of information technology is expected to improve the quality of BK services, but on the other hand it also has the potential to cause various obstacles both in terms of facilities, understanding, and ethics of use. The purpose of this study is to determine the positive and negative impacts of the use of information technology in the implementation of guidance and counseling services by BK teachers at SMKN 1 Sumbar. This study uses a quantitative approach with a comparative descriptive research type. The study population was 170 students, with a sample of 113 people selected using a sampling technique of 25–30% of the population. The research instrument was a questionnaire with a Likert scale, which has been tested for validity and reliability. The results of the study indicate that the use of information technology in BK services has a positive impact in the form of increased communication and information exchange, ease of access to information, and encouraging collaboration and exchange of ideas. However, negative impacts were also identified, such as students' lack of understanding of information technology media and a tendency to misuse social media in the learning process.Thus, the use of information technology in guidance and counseling services at SMKN 1 Sumbar has been proven to increase service effectiveness, although additional support facilities, improved digital literacy, and supervision are still needed to minimize negative impacts.